Expression of Enhancer-Binding Protein CEBPA mRNA and Protein in Ovarian Cancer and Its Relationship With Pathobiological Characteristics - Mi, Shufang; Zhang, Limei; Li, Mo; Dong, Zhiting; Tian, Chenchen; Fu, Minwen (Frontiers in Surgery, 2022)
Ovarian cancer is a common malignant tumor, its early onset is hidden, lack of specific symptoms, the location of the lesion is particularly hidden, which makes it difficult to find ovarian lesions by general detection, making it difficult to make an early clinical diagnosis. Therefore, it is still the focus and difficulty of ovarian cancer research to find the means of early diagnosis and prognosis of ovarian cancer. Cytosine-cytosine-adenosine-adenosine-thymidine (CCAAT) enhancer-binding protein α (CEBPA) has been proved to be involved in cell metabolism, proliferation, and differentiation. In this study, the expression of CEBPA mRNA and protein in normal ovary, epithelial ovarian cyst, ovarian borderline tumor, and ovarian cancer was detected, the relationship between CEBPA and pathobiological characteristics of ovarian cancer was discussed, and its influence on the prognosis of patients with ovarian cancer was analyzed. The results showed that the expression of CEBPA mRNA and protein in patients with ovarian borderline tumor and ovarian cancer is high, and the expression of CEBPA has no obvious correlation with the pathobiological characteristics of patients with ovarian cancer, and the high expression of CEBPA has an important value in the diagnosis of ovarian cancer, and it is also a poor prognostic factor of the disease.